Technology Acceptance Model: the use of E-Study Aplications in E-Learning - Sefriani, Rini; Zefriyenni; Rina Sepriana (Journal of Education Technology, 2022)
The use of the Estudy application in e-learning by students of the Faculty of Engineering must be carried out due to the demands of circumstances that require studying from home due to the Covid-19 pandemic. The purpose of this study is to analyze how the acceptance of e-study application technology by Engineering faculty students during online learning is carried out. This type of research is quantitative by surveying students. The model used for analyzing technology acceptance is that proposed by Davis. The instrument in this study was a questionnaire that was distributed to students via the Google form link which was distributed online. The sample in this study amounted to 128 people. The data analysis technique used is a correlation. The study results showed that engineering faculty students showed positive attitudes and behaviors in using the Estudy application as an educational platform in e-learning during the Covid-19 pandemic. Thus the use of the e-study application during the Covid-19 pandemic by utilizing the Estudy application by engineering faculty students had a positive effect on learning from home in the form of e-learning. Future e-study applications can be used as e-learning media by students in lectures.